Opinions of high school students about teacher and teaching in selected high school - Fajutag, Brigida V. 1932- (1958)
The principal purpose of this investigation was to determine the attitude of high school students toward their teachers and the teaching profession. Four public high school in Caloocan, Rizal were selected. Information was obtained from the students by means of a three-page questionnaire. For the entire group the characteristics most frequently checked listed in rank order were: (1) having no favorites among students; (2) have an understanding of students' problem; (3) have a good sense of humor; and (4) was fair in grading. They indicated a dislike for the following characteristics of teacher: (1) partiality in grading; (2) inadequate explanation of lessons; (3) having favorites among the students; (4) inability to take jokes; (5) possession of poor speaking voice; and (6) not being good-looking.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Teachers -- Philippines -- Manila; Teaching